EFEKTIFITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SMP NEGERI 8 PADANGSIDIMPUAN - Novia Andriani; Rahmatika Elindra; Agus Saleh (JURNAL MathEdu (Mathematic Education Journal), 2021)
The aim of this study is to describe the effectiveness of using Realistic Mathematic Education approach in improving students’ communication ability on the topic of triangles at the seventh grade students of SMP Negeri 8 Padangsidimpuan. The research was conducted by applying experimental method (one group pretest post test design) with 22 students as the sample and they were taken by using cluster random sampling technique from 176 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using Realistic Mathematic Education approach was 3,7 (very good category) and (b) the average of students’ triangles achievement before using Realistic Mathematic Education approach was 64.99 (enough category) and after using Realistic Mathematic Education approach was 78.86 (good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 22) and N-Gain formulation, the result showed the significant value was less than 0.05 (0.000<0.05) and g= 0.52 (medium category). It means, using Realistic Mathematic Education approach was able to improve students’ communication ability on the topic of triangles with medium category at the seventh grade students of SMP Negeri 8 Padangsidimpuan.